Analisis Peran Dan Dampak Bantuan Hukum Oleh Lembaga Yayasan Harapan Riau Sejahtera Dalam Mewujudkan Keadilan Bagi Masyarakat - Samariadi Samariadi; Maria Dwinoverine; Amelia Jelita Putri; Muhammad Firdaus Eriyan; Sarmauli Br Simamora; Tengku Falqih Muhammad Alif (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research evaluates and enhances the effectiveness of legal aid provided by the Legal Aid Institution of the Yayasan Harapan Riau Sejahtera, which focuses on economically disadvantaged communities. The research methodology involves causal analysis, interviews, informal dialogues, and participatory observations. The author examines the case handling process, the sustainability of legal solutions, as well as client satisfaction and understanding. While the institution makes a positive contribution to access to justice, the research identifies implementation challenges. The evaluation encompasses case handling efficiency, resource availability, and efforts to improve legal understanding within the community. This study provides in-depth insights and recommendations to improve service effectiveness, with implications as a basis for changes in the legal aid institution and related stakeholders to optimize legal services for those in need.